Effect of combination of organosulfur and polyphenols organic fungicide on Ganoderma-infected oil palm seedlings - Yusup, Ciptadi Achmad; Eris, Deden Dewantara; Mulyatni, Agustin Sri; Pradana, Mahardika Gama; Widiastuti, Happy; Santoso, Djoko (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2026)
The curative potential of an organic fungicide against Ganoderma boninense was previously assessed in vitro and yielded promising results. This organic fungicide was formulated using a combination of organosulfur compounds and polyphenols (OSC-P) as active ingredients. This study aimed to evaluate the effectiveness of OSC-P application in controlling basal stem rot (BSR) disease in infected oil palm seedlings of different varieties and to determine the optimum application dose. Two oil palm varieties were used: a G. boninense-susceptible variety and a moderately tolerant variety. The seedlings were artificially infected with G. boninense using inoculated rubber wood blocks (RWB). OSC-P was applied to 16-week-old seedlings by soil drenching at a volume of 200 mL per plant at 2-week intervals for 24 weeks. A total of six treatments, including controls, were arranged with four replications and observed at 4-week intervals. Each replication consisted of 10 seedlings. Observed parameters included disease incidence, disease severity, and vegetative growth parameters. The results showed that OSC-P application significantly reduced the incidence and severity of BSR disease in infected oil palm seedlings. BSR symptoms were less severe in the moderately tolerant variety than in the susceptible variety; however, disease incidence did not differ significantly between the two varieties. The optimum application dose of OSC-P was 0.8% (v/v), and variations in application dose did not significantly affect disease incidence or severity at 24 weeks after application. These findings are expected to complement existing preventive strategies for BSR management.